Investigação dos efeitos protetores de um modulador alostérico positivo do mGluR5 em modelo de toxicidade induzida por amiloide-beta e em modelo murino transgênico de doença de Alzheimer - Paula Maria Quaglio Bellozi (2018)
Alzheimer’s disease (AD) is the most incident neurodegenerative disorder. The role of metabotropic glutamate receptors (mGluRs) in neuronal cell death observed in AD is not completely understood. Recent data indicates that CDPPB, a positive allosteric modulator of mGluR5, has neuroprotective effects in other central nervous system pathologies. Thus, the present work aimed to investigate the effect of CDPPB treatment in amyloid-β (Aβ) induced pathological alterations and in an AD mouse model. Aβ induced cell death in cultures of hippocampal neurons prepared from newborn C57Bl/ 6 mice, which was prevented by CDPPB (1nM). Male C57Bl/6 mice underwent stereotaxic surgery for unilateral intra-hippocampal Aβ injection, which induced memory deficit in the object recognition task and contextual conditioned fear, as well as neurodegeneration. Treatment with CDPPB for 8 days (1 or 5 mg / kg, i.p.), starting either on the same day of surgery or after 1 week, was able to reverse cognitive deficits, neurodegeneration, and to increase BDNF hippocampal levels. Thy1APPLond/Swe+ (T41) transgenic mice at 14 months of age presented cognitive deficits and behavioral changes, reduction of neuronal viability, gliosis and Aβ accumulation. Treatment with CDPPB (5mg / kg, i.p.) for 28 days was not able to reverse cognitive deficit. However, CDPPB increased neuronal viability and partially reduced gliosis without inducing hepatotoxicity. Thus, despite not preventing memory loss in transgenic mice, CDPBB improved cognition after Aβ injection, and has a potential neuroprotective effect, especially associated with the prevention of neuronal loss. Therefore, it should be considered additional evaluations of the drug in more chronic studies.